Pembrolizumab plus pemetrexed and platinum in nonsquamous non-small-cell lung cancer: 5-year outcomes from the phase 3 KEYNOTE-189 study - Garassino, Marina; Gadgeel, Shirish; Speranza, Giovanna; Felip, Enriqueta; Esteban, Emilio; Dómine, Manuel; Hochmair, Maximilian; Powell, Steven F.; Bischoff, Helge; Peled, Nir; Grossi, Francesco; Jennens, Ross R.; et al. (Journal of clinical oncology, 2023)
Clinical trials frequently include multiple end points that mature at different times. The initial report, typically on the based on the primary end point, may be published when key planned co-primary or secondary analyses are not yet available. Clinical Trial Updates provide an opportunity to disseminate additional results from studies, published in JCO or elsewhere, for which the primary end point has already been reported. - - We present 5-year outcomes from the phase 3 KEYNOTE-189 study (ClinicalTrials.gov identifier: NCT02578680). Eligible patients with previously untreated metastatic nonsquamous non-small-cell lung cancer without EGFR/ALK alterations were randomly assigned 2:1 to pembrolizumab 200 mg or placebo once every 3 weeks for up to 35 cycles with pemetrexed and investigator's choice of carboplatin/cisplatin for four cycles, followed by maintenance pemetrexed until disease progression or unacceptable toxicity. Primary end points were overall survival (OS) and progression-free survival (PFS). Among 616 randomly assigned patients (n = 410, pembrolizumab plus pemetrexed-platinum; n = 206, placebo plus pemetrexed-platinum), median time from random assignment to data cutoff (March 8, 2022) was 64.6 (range, 60.1-72.4) months. Hazard ratio (95% CI) for OS was 0.60 (0.50 to 0.72) and PFS was 0.50 (0.42 to 0.60) for pembrolizumab plus platinum-pemetrexed versus placebo plus platinum-pemetrexed. 5-year OS rates were 19.4% versus 11.3%. Toxicity was manageable. Among 57 patients who completed 35 cycles of pembrolizumab, objective response rate was 86.0% and 3-year OS rate after completing 35 cycles (approximately 5 years after random assignment) was 71.9%. Pembrolizumab plus pemetrexed-platinum maintained OS and PFS benefits versus placebo plus pemetrexed-platinum, regardless of programmed cell death ligand-1 expression. These data continue to support pembrolizumab plus pemetrexed-platinum as a standard of care in previously untreated metastatic non-small-cell lung cancer without EGFR/ALK alterations.